Effects of salbutamol on serum potassium level and electrocardiography in experimental hyperkalemia in rabbits - Ramazan Bal; Ramazan Durgut; Sefa Çelik (Eurasian Journal of Veterinary Sciences)
In this study 12 New Zealand Rabbits were used, which were divided into 2 groups, positive control and salbutamol. For induction of hyperkalemia, 300 mM KCI solution (in isotonic NaCI) was infused at 0.5 ml/kg/min for 15 minutes via v.auricularis. For salbutamol group, isotonic saline solution containing 6 pg salbutamol per ml was administered at 0.35 ml/kg/min for 30 minutes. Whereas, for positive control group, after the first 15 minutes only isotonic NaCI solution was administered. ECG recordings were performed every 3 minutes in Ihe period of the first 45 minutes and (hen at 60th and 90th minutes. Blood samples were collected from the other ear at 0th, 15th, 30th, 60®1 and 90m minutes, and the potassium level was measured from blood serum. Potassium ievel was measured to be approximately 3,9 mmol/L at time zero. With potassium infusion, the level of the serum potassium increased above 6.5 mmol/L. Application of salbutamol caused the serum potassium level to return to the control level, and also caused the ECG changes (flattness ol P wave, widening of QRS complex and bradycardia) induced by hyperkalemia to become normal. On the other hand, it was found thai the serum potassium level continue to increase and that ECG changes did not become normal in positive control group. In conclusion, salbulamol which is a p2 agonist might be used for treatment purpose in hyperkalemia.